2019
DOI: 10.3389/fpsyt.2019.00498
|View full text |Cite
|
Sign up to set email alerts
|

Placebo- and Nocebo-Effects in Cognitive Neuroenhancement: When Expectation Shapes Perception

Abstract: Objective: The number of students using prescription drugs to improve cognitive performance has increased within the last years. There is first evidence that the expectation to receive a performance-enhancing drug alone can result in improved perceived and actual cognitive performance, suggesting a substantial placebo effect. In addition, expecting a placebo can result in lower perceived and actual cognitive performance, suggesting a nocebo effect. Yet, the underlying mechanisms of these effects rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…A recent study 46 (N = 58) showed that OLP reduced test anxiety but did not include test performance as an outcome variable. Previous studies using deceptive placebo treatments or manipulations of expectancy on objective outcome parameters of cognitive performance had yielded very mixed results 47 , 48 , suggesting that placebo effects on cognitive performance might be complex and dependent on a variety of factors. Our results suggest that the same applies to open-label application of placebos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study 46 (N = 58) showed that OLP reduced test anxiety but did not include test performance as an outcome variable. Previous studies using deceptive placebo treatments or manipulations of expectancy on objective outcome parameters of cognitive performance had yielded very mixed results 47 , 48 , suggesting that placebo effects on cognitive performance might be complex and dependent on a variety of factors. Our results suggest that the same applies to open-label application of placebos.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, differential effects on subjective and objective outcome parameters has also been observed in traditional hidden placebo trials 15 , 49 as well as in OLP treatment of chronic back pain patients 18 . Winkler and Hermann 48 for instance have shown that a placebo, which was experimentally linked to either a positive (i.e., placebo-nootropic) or negative expectation (i.e., placebo-antihistamine agent), improved perceived but not actual cognitive performance in a standardized test.…”
Section: Discussionmentioning
confidence: 99%
“…Munro et al cannot rule out the possibility that neuroenhancement prevented declines in academic performance, but conclude that students who engaged in neuroenhancement showed no increases in their academic performance and gained no detectable advantages over their peers [45]. Prescription drug consumption could affect neuroplasticity and may, therefore, result in deterioration of cognitive performance and even the personality of users [47].…”
Section: Discussionmentioning
confidence: 99%
“…Another type of risk regarding the safety of cognitive neuroenhancers is addiction. A nationwide survey estimates that almost one in twenty misusers of prescription drugs meet the criteria for dependence or abuse [47]. Physiological changes in the brain caused by repeated use could lead to increased use of these drugs in more demanding academic environments [48].…”
Section: Discussionmentioning
confidence: 99%
“…The statistical correlations between pain relief and functional outcomes across the disease entities in the current study are consistent with a relevant effect of LDRT. Although the study was uncontrolled, the lack of blinding is not expected to have had any significant impact on the objective functional tests (57).…”
Section: Discussionmentioning
confidence: 99%